Investigation of the ADA Enzyme and Lipid Profile in Children Infected with Enterobius Vermicularis - Esam Akram, Haneen; Al-Warid, Harith (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
Adenosine deaminase (ADA) and lipid profile may be associated with some diseases. Parasitic diseases have also been reported to be associated with ADA and lipid profiles. This study aimed to evaluate ADA, lipid profile, and total protein among children infected with E.vermicularis. This research was carried out in Baghdad province from October 2021 to the end of March 2022. One hundred samples were collected from both sexes, ranging in age from (3-16) years. They all underwent examination for ADA, cholesterol, low-density lipoprotein (LDL), high-density lipoprotein (HDL), and total protein levels. Results showed no significant differences between E.vermicularis positive group and E.vermicularis negative group regarding ADA, LDL, and triglycerides, although their levels were lower in children with E. vermicularis infection versus the control. In contrast, results showed significant differences (P˂0.05) in cholesterol, HDL, and total protein between E.vermicularis positive group and E.vermicularis negative group. All these values decreased significantly compared to the control group.